Starting and specialising ages across Olympic sports: A cross-sectional study in an international sample of elite athletes - Descheemaeker, K.; De Bosscher, V.; Shibli, S. (Book of Abstracts EASM, 2023)
AIM AND RESEARCH QUESTIONS Talent development models are frameworks that can be used to develop potential athletes. This paper intends to adapt talent development models to specific sports by investigating starting and specialising ages across Olympic disciplines. Three key research questions guided this study: (1) What are sport specific starting and specialisation ages in elite athletes? (2) Is there a relationship between one`s starting and specialising age? (3) How can we classify sports according to the starting and specialisation ages?